The Macroeconomics Factors Effecting Economic Growth of Laos from 2012-2021 - THAMMAVONG, Phiengkham; SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone; PHIMPHISANE, Thavisay; SENGDARA, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this analysis of macroeconomic factors affecting the economic growth of Lao PDR. This research is intended to (1) Analyze the economic growth situation in Lao PDR in 2012 -2021 and (2) Macroeconomic factors affecting the economic growth in Lao PDR in 201 2 -2021. By collecting information that has been archived compile, interpret, consider , select and analyze descriptive statistical model and inferential statistics to find a value percentage , parameter value of regression line equation with OLS through E-view 8. The analysis results were found that: Laos economy situation PDR has continued steady growth during 2012-2018 and has decreased by deficit 7.82% in 2019-2021 as the impact of new strain virus disease outbreaks (Covid – 19), however during the crisis makes the value of the trade surplus reached 1,814,393,000 US dollars due to tariff reductions import goods from Lao PDR to China totally 8,256 items. In terms of macroeconomic factors which affects Laos economy growth are: Inflation and economic growth are related in opposite directions as if inflation increase 1% will have an effect on economic growth decline 0.06 US dollars. Exchange rates and economic growth are related in opposite directions if the exchange rate increased 1 US dollar will have an effect on economic growth converted down to 1.94 US dollars. For Export and economic growth are related in the same direction if the export increased 1 US dollar will effect economic growth by increased variability 0.26 US dollars. For Import and economic growth are related in opposite directions if import increased 1 US dollar will have an effect on economic growth decrease 0.28 US dollar.